Representasi Feminisme dalam Lirik Lagu “Anganku Anganmu” Karya Raisa Feat Isyana Sarasvati - Putri Yusma Dewi Siagian (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to study the meaning of feminism contained in the lyrics of Raisa and Isyana Sarasvati's song